Thresholds for vestibular and cutaneous perception and oculomotor response induced by galvanic vestibular stimulation - Nguyen, Thanh Tin; Kang, Jin-Ju; Oh, Sun-Young (Frontiers in Neurology, 2022)
Objectives In this study, the specific threshold intensities and response characteristics of galvanic vestibular stimulation (GVS) on vestibular (conscious) and cutaneous (detrimental) perception as well as oculomotor nystagmus (reflex) were determined. Methods The threshold intensities for vestibular and cutaneous perception and oculomotor response induced by GVS were determined in 25 right-handed healthy subjects (32.6 ± 7.2 years of age; 56% female). The subjects were seated upright, and eye movements were recorded while a direct GVS current was applied with paradigms of cathode on the right and anode on the left (CRAL) and also cathode on the left and anode on the right (CLAR). Results Subjects experienced dizziness, sense of spinning, or fall tendency, which was more frequently directed to the cathode (76%) than the anode (24%, p < 0.001, chi-square one-variable test) at mean current greater than 0.98 ± 0.29 mA (mean vestibular threshold). The current also triggered a more frequent mild tingling sensation at the cathode (56%) than the anode (30%) or on both sides (14%; p = 0.001, chi-square one-variable test) when above the mean cutaneous threshold of 0.9 ± 0.29 mA. Above the mean oculomotor threshold of 1.61 ± 0.35 mA, combined horizontal and torsional nystagmus was more frequent toward the cathode (86%) than toward the anode (p < 0.001, chi-square one-variable test). The mean oculomotor threshold was significantly higher than both the vestibular (p < 0.001, Mann–Whitney U-test) and cutaneous (p < 0.001, Mann–Whitney U-test) thresholds, which were comparable (p = 0.317, Mann–Whitney U-test). There was no significant disparity in these specific thresholds between the two GVS paradigms. The vestibular threshold was significantly higher in males than in females [1 (0.5–1.25) mA vs. 0.75 (0.625–1.125) mA, Z = −2.241, p = 0.025, Mann–Whitney U-test]. However, the thresholds of cutaneous perception and oculomotor response did not differ by sex. Conclusion The findings indicate that thresholds for vestibular and somatosensory perception are lower than the oculomotor threshold. Therefore, a strategy to reduce GVS current intensity to the level of vestibular or somatosensory perception threshold could elicit beneficial vestibular effects while avoiding undesirable effects such as oculomotor consequences.